(untitled) (Training and Practice : Journal of Educational Sciences, 2007)
The study presents the status of teachers in the mirror of statistics, then analyses that in the era of dualism on which competence could the authors of pedagogical books imagine the effective educational work. The study looked for answers to the following questions: Can the ideal picture of teacher be reconstructed on the evidence of the pedagogical books? Is there any noticeable change on the evidence of the analysed books in the given period of time? To verity her supposition the author has chosen the method of study of sources. Analysis of the published pedagogical books in the given period of time is suitable for presenting the picture of ideal teacher typical of the era. In her summary we can see that 19th century educational books draft a lot of similar expectations towards the ideal teacher. The authors believe that successful teaching can be achieved by pedagogical competence and they prefer knowledge and skill to emotional features. They think it is necessary to love the profession, to be educated and methodologically trained as the main features of the ideal teacher but moral features, knowledge of children and love of children are important parts of a teacher’s profession. Analysing the educational textbooks we can see that the picture of teacher emerging from the works consists of the whole range of expectations.